Effectiveness of E-Learning Media in Asynchronous Learning: A Case Study in Higher Education - Patongloan, Asce; Prayogi, Ratnawati; Rumambi, Freddy J.; Inkriwang, Alfred (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Asynchronous learning is important to worldwide higher education's digital transition. Despite extensive technology usage, issues about asynchronous learning media quality and pedagogy persist. Most studies have used the participants' final exam scores to evaluate the effectiveness of asynchronous learning. Consequently, this study seeks to evaluate the efficacy of e-learning media in facilitating asynchronous learning within the Officer Cadet Advancement Training Program (CATP or PASIS) at the higher education level. The primary focus of the research is to identify the level of participant engagement, their perceptions of the effectiveness of e-learning media, and the challenges faced by both participants and facilitators during the learning process. This research employs a mixed-methods approach, combining quantitative data collected through questionnaires administered to 47 respondents at Poltekpel Barombong and qualitative data gathered through in-depth interviews with participants, instructors, and e-learning administrators. The findings indicated that most participants regularly access the platform, complete assignments on time, and feel comfortable with self-directed learning. However, forum participation and learning motivation vary, especially among e-learning novices. While most respondents say e-learning media helps them understand the topic, they still need direct instruction, especially for technical content. Internet instability, lack of two-way communication, and participant digital incompetence are the key issues. Improved material quality, facilitator training, and solid support mechanisms improve e-learning deployment.